2005
DOI: 10.1111/j.1365-2958.2004.04455.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli ribosomal RNA transcription: regulatory roles for ppGpp, NTPs, architectural proteins and a polymerase‐binding protein

Abstract: SummaryRibosomal RNA transcription can limit the rate of Escherichia coli growth and is subject to complex regulation. Somehow, the cell is able to sense the general nutritional environment and adjust rRNA transcription so that an appropriate number of ribosomes is produced. This review discusses the current state of affairs, including recent information about the involvement of two nucleotide regulators, two architectural protein regulators, one new co-regulator and stalled ribosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 34 publications
3
65
0
1
Order By: Relevance
“…rRNA transcription initiation is also regulated by the concentration of the first nucleotide in the transcript (8,14) and by at least one DNA binding factor, the 11.2-kDa Fis protein (15). Together, ppGpp, DksA, the concentration of the first NTP (iNTP), and Fis match ribosome synthesis rates to the availability of nutrients (8,11,(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…rRNA transcription initiation is also regulated by the concentration of the first nucleotide in the transcript (8,14) and by at least one DNA binding factor, the 11.2-kDa Fis protein (15). Together, ppGpp, DksA, the concentration of the first NTP (iNTP), and Fis match ribosome synthesis rates to the availability of nutrients (8,11,(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The oligomerization of H-NS is, therefore, essential for preferential binding and stabilization of the multimeric nucleoprotein complex (Spurio et al 1997). A recent study of an E. coli ribosomal gene promoter rrnB P1 has suggested that repression involves DNA looping and that the loop is closed by the association of two patches of H-NS-bound DNA in which the RNP is trapped, instead of being excluded (Schroder and Wagner 2000;Dame et al 2002;Dame 2005;Gralla 2005). According to this model, expression from an H-NS repressed promoter should require disruption of the nucleoprotein complex and the DNA loop by transcription factors.…”
mentioning
confidence: 99%
“…FIS is a nucleoid-binding protein involved in global regulatory circuits related to repression of genes that are not required Role of FIS in aromatic catabolic pathways of E. coli under conditions of optimal growth (González-Gil, et al, 1996). It is also well known that FIS acts as a positive regulator of the transcription of the genes that encode stable RNA species, such as rRNA and tRNA (Ross et al, 1990;Bosch et al, 1990;Nilsson & Emilson, 1994;Gralla, 2005). To investigate the putative role of FIS in the hpa regulatory system, we generated a FIS mutant of the E. coli strain W, named W16 (Table 1).…”
Section: Pg Repression Is Relieved In a Fis Mutant When Cultured In Lmentioning
confidence: 99%